2017
DOI: 10.1039/c7ta03497k
|View full text |Cite
|
Sign up to set email alerts
|

Metallic 1T MoS2 nanosheet arrays vertically grown on activated carbon fiber cloth for enhanced Li-ion storage performance

Abstract: Metallic 1T-phase MoS2 nanosheets have a high concentration of edge active sites and other defects, for enhanced Li-ion storage performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
170
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 263 publications
(184 citation statements)
references
References 53 publications
13
170
1
Order By: Relevance
“…Theselected-area electron-diffraction (SAED) image clearly indicates the phase transformation (Figure 2c-left), and the SAED 1D profile of the annealed sample demonstrates clearly the (100) and (106) lattice facets of 2H-MoS 2 ,w hich are pretty weak in the as-synthesized 1T-MoS 2 /NiS 2 (Figure 2c-right, Figure 2d). [21] Furthermore,the 2H phase MoS 2 in the 2H-MoS 2 /NiS 2 was confirmed through HAADF-STEM and simulation (Figure 2e,f). [15] Thec lear honeycomb lattice in the image indicates the coordinated Satoms with Mo sites overlap to be enhanced, even though the Satomic number is quite low.…”
mentioning
confidence: 76%
“…Theselected-area electron-diffraction (SAED) image clearly indicates the phase transformation (Figure 2c-left), and the SAED 1D profile of the annealed sample demonstrates clearly the (100) and (106) lattice facets of 2H-MoS 2 ,w hich are pretty weak in the as-synthesized 1T-MoS 2 /NiS 2 (Figure 2c-right, Figure 2d). [21] Furthermore,the 2H phase MoS 2 in the 2H-MoS 2 /NiS 2 was confirmed through HAADF-STEM and simulation (Figure 2e,f). [15] Thec lear honeycomb lattice in the image indicates the coordinated Satoms with Mo sites overlap to be enhanced, even though the Satomic number is quite low.…”
mentioning
confidence: 76%
“…However, the metallic MoS 2 reveals a unique (001) peak around 7.3°, which evidences an additional layer separation of 0.55–0.60 nm during restacking . This specific peak was reported and explained as an expanded layer structure in 1987 by Frindt et al followed by numerous recent researchers . The appearance of this (001) peak before 10° is the most conventional identification trait of metallic MoS 2 using XRD.…”
Section: Characterizationsmentioning
confidence: 86%
“…The same group proved that it is also possible to achieve the metallic MoS 2 in DMF without using any water by the reaction of molybdenum chloride and thioacetamide at 200 °C in autoclave . Pan et al reported that metallic MoS 2 can also be fabricated by Na 2 MoO 4 •2H 2 O and L‐cysteine in a mixed solvent of DMF and water with a DMF to water ratio of 1.5:1 at 200 °C for 12 h (Figure b). The layer distance of the as‐prepared metallic MoS 2 is around ≈0.90 nm that is much larger than the traditional layer distance of ≈0.62 nm .…”
Section: Fabrication Methods For Metallic Mos2mentioning
confidence: 95%
See 2 more Smart Citations